The Role of Teacher Support in Student Engagement at Private Madrasah Tsanawiyah - Nurva Dillatul Vatin (Institut Agama Islam Sumatera Barat, 2024)
Student engagement is a form of student involvement in learning, involving cognitive, emotional, and behavioral aspects. In the school environment, teacher support is one of the factors influencing student engagement. This study aims to determine the role of teacher support in student engagement at MTsS X. The research employs a quantitative method involving 30 student participants. Participant recruitment utilizes a saturated sampling technique. Data collection involves scales for student engagement and teacher support. The data analysis method used is simple linear regression analysis. The research findings indicate that teacher support significantly contributes to student engagement. The magnitude of the influence that teacher support has on student engagement is 22%. The findings of this research can serve as a reference for schools, especially teachers, to support students during learning. Support from teachers can enhance student engagement and participation in the learning process.